(untitled) (Palíndromo, 2025)
This article analyzes the group exhibition “De uma alegria para sempre não destinável”, held in 2024 by the FURTACOR Collective at Casa Caipora Centro Cultural, in Vitória/ES, with the aim of reflecting on how autonomous curatorial practices, articulated in independent cultural spaces, can contribute to the construction of more inclusive and plural cultural ecosystems, expanding the debate on contemporary art in Espírito Santo. Starting from a broader contextualization of the topic, we situate the exhibition in a panorama that allows understanding its specificities and establishing parallels with similar initiatives in other contexts. For this purpose, we adopt an essayistic approach, taking the experience report as a methodological compass, which enables us to articulate contextual reflection and self-critical analysis of the processes and practices developed in the exhibition, highlighting their challenges and potential in the strengthening of collaborative networks advocating alternative modes of production, circulation, and reception of art. The reflections indicate that, even in the face of limited resources, the experience energized the local art-cultural scene beyond the structures and traditional circuits of dissemination. By promoting the redistribution of visibility, recognition, and legitimacy of productions, agents, and spaces frequently marginalized, the initiative pointed to alternative vectors for democratizing access to art in the region. It is concluded that such actions not only challenge institutional limits and hierarchies but also demonstrate the potential of self-management as a means to expand the intersections between the sensitive and the political, reaffirming the role of autonomous initiatives and independent spaces in constructing a more plural and accessible cultural landscape.